2017
DOI: 10.1371/journal.pone.0173118
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of porous silicon as hydroxyapatite host matrix of biomedical applications

Abstract: In this work, porous-silicon samples were prepared by electrochemical etching on p-type (B-doped) Silicon (Si) wafers. Hydrofluoric acid (HF)-ethanol (C2H5OH) [HF:Et] and Hydrofluoric acid (HF)-dimethylformamide (DMF-C3H7NO) [HF:DMF] solution concentrations were varied between [1:2]—[1:3] and [1:7]—[1:9], respectively. Effects of synthesis parameters, like current density, solution concentrations, reaction time, on morphological properties were studied by scanning electron microscopy (SEM) and atomic force mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…These results are in good agreement with previously reported studies regarding the lack of antimicrobial properties of hydroxyapatite [20,59,60]. Moreover, previous studies [15,[56][57][58][59][60][61][62][63][64] reported that the antifungal effect of samarium could be explained by the fact that samarium ions have the ability to attach to the cell membrane leading to changes of its permeability. Furthermore, samarium ions that are released from the composite matrix could disrupt the bacterial membrane integrity thus affecting a multitude of cellular processes such like adhesion, ion conductivity and cell signaling [61].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in good agreement with previously reported studies regarding the lack of antimicrobial properties of hydroxyapatite [20,59,60]. Moreover, previous studies [15,[56][57][58][59][60][61][62][63][64] reported that the antifungal effect of samarium could be explained by the fact that samarium ions have the ability to attach to the cell membrane leading to changes of its permeability. Furthermore, samarium ions that are released from the composite matrix could disrupt the bacterial membrane integrity thus affecting a multitude of cellular processes such like adhesion, ion conductivity and cell signaling [61].…”
Section: Resultssupporting
confidence: 93%
“…Thus, the development of 5SmHAp coatings with enhanced osteoblastic cell response given by the hydroxyapatite matrix and possessing antibacterial activity due to the presence of samarium ions could lead to a better outcome of bone graft implantation. The choice of Si as a substrate started from the intention to extend the applicability of these biocompatible materials with antimicrobial properties from dental field to devices that could be used in tissue engineering [62] or human prosthetic [63] in order to prevent postoperative infections. Ruffino and Torrisi [64] in their studies regarding the influence of interaction between film and substrate on the nanoscale film morphology showed that between Ag films deposited on SiO 2 /Si and TiO 2 /Ti substrates exist various differences.…”
Section: Resultsmentioning
confidence: 99%